ANALISIS KEBUTUHAN PENILAIAN SPRITUAL PADA PEMBELAJARAN ABAD 21 - Emelda Thesalonika Manalu; Edy Surya (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
The assessment instrument used as a mandatory reference by teachers and students in the 21st century learning process. 21st Century learning integrates literacy skills, knowledge skills, skills and attitudes as well as mastery of technology. Therefore, an assessment that is not only cognitive is needed. This study aims to analyze the need for spiritual assessment in 21st century learning. This study used a qualitative method with data acquisition through observation and interviews with principals and teachers. The results showed that principals and teachers needed spiritual assessment.